PENGGABUNGAN (MERGER) PERSEROAN TERBATAS DI INDONESIA DAN DAMPAKNYA TERHADAP PEKERJA - SUSPIM G P NAINGGOLAN (PREMISE LAW JURNAL, 2016)
In the regulation on merger in Indonesia, a company that wants to merge is a corporation. Therefore, a company which is not a corporation does not comply with the regulation on merger as stipulated in Law No. 40/2007 on Corporation and Implementation. Merger of corporations on employees has positive and negative impacts. The positive impact of the merger of corporations is that the worker still work and reemployed so that they will get better wages and can work for the merging corporation. The negative impact of the merger of corporations is that the corporation dismisses its employees by only give them severance pay, money for the length of service, and compensation. The type of protection for the employees who are reemployed is that the merging corporation has to accept the transfer of all rights and obligation from the corporation that wants to merge, including the rights and obligation of the employees since they must not be harmed. It depends on whether they voluntarily quit from their job or they do not want to work for the merging corporations. Employees have the right to get severance pay, money for the length of service, and compensation. Theory of justice by Jhon Rawls states that the type of protection for employees is not fair due to efficiency and merger for the sake of the advantage of a certain number of people who harm other people (employees) like the rule which regulates the dismissal of employees. Keywords: Corporation, Merger, Employees